Template-Free Synthesis of Star-Like ZrO2 Nanostructures and Their Application in Photocatalysis - Xue-Yu Tao; Jie Ma; Rui-Lin Hou; Xiang-Zhu Song; Lin Guo; Shi-Xiang Zhou; Li-Tong Guo; Zhang-Sheng Liu; He-Liang Fan; Ya-Bo Zhu (Advances in Materials Science and Engineering)
Star-like nano-ZrO2 has been synthesized using Zr(NO3)4·5H2O as zirconium source by a hydrothermal process without any template and surfactant. The structure of the as-prepared ZrO2 powder was investigated by multiple advanced analytical methods. The results showed that CH3COO− and NO3− had great effects on the formation of star-like ZrO2 nanostructures. The as-prepared ZrO2 had a superior catalytic activity, and the reason for it was analyzed by UV-Vis diffuse reflectance spectroscopy. The effect of raw material ratios on the photocatalytic property of ZrO2 was studied. The synthesized ZrO2 showed a narrow bandgap (3.50–3.85 eV) and an excellent photocatalytic activity, and the degradation of RhB was up to nearly 100% in 30 min with this photocatalyst.